Socialization of Da'wah through Technology Media Information with the Theme of Understanding Muslim Attitudes Facing the Covid-19 Pandemic Disaster - Irfan Santosa; Ghusni Darodjatun (ASEAN Journal of Empowering Community, 2021)
The covid-19 virus pandemic in Indonesia has been taking place since February 2020, which almost knocked out all sectors of the economy, industry, trade and human mentality. Data as of April 13, 2020 shows that the number of people in Indonesia contaminated with the covid-19 virus totals 4557 people, with the number of deaths of 399 people and patients cured reached 380 people (Source detik.com). From this data, the Government of Indonesia enacts and urges all people to stay at home or Stay at Home. With the program to stay at home, many people do all activities from home from work, study, worship done at home together with family. The implementation of staying at home from March 13, 2020 until now makes some people feel saturated, can't wait to stay at home so that many people are not disciplined in doing this program and still do regular activities in the midst of the covid-19 pandemic. The impact of impatience, indiscipline and disorderly behavior is what results in the number of contaminated sufferers every day is increasing. Therefore, it is necessary to socialize about the understanding that should be done especially by every Muslim in the face of the covid-19 pandemic disaster. The method used is to make a video of da'wah containing a short message about patience in the face of disasters that last approximately 3 minutes and upload it online then share the online link through the group in Whatsapp group. The hope of this devotion program is that the community, especially Muslims, will be encouraged and self-conscious to be able to stay at home until the End of the covid-19 pandemic. The results of this program after the video message was uploaded through Youtube then disseminated through Whatsapp group and watched approximately 150 times there are 25 people responded by sending a comment message to this video and 25 people will try to remain patient in the face of the test and implement government programs to stay home until the pandemic outbreak subsides.